O ACONSELHAMENTO EM HIV-AIDS/IST NO CONTEXTO DA ATENÇÃO BÁSICA EM SAÚDE - Santos, Emalline Angélica de Paula (2019)
The SIDA epidemic in the 1980 mobilized society and public entities in the search for effective prevention strategies to control and combat the epidemic. Counseling emerged as a practice aimed at providing emotional, educational, and risk assessment support in different settings, especially at the Counseling and Counseling Centers. In the last decade, there has been a process of decentralization of VIH-SIDA/STI care to basic care, with the incorporation of rapid tests for VIH, syphilis and hepatitis B and C. In this way, our objective was to understand how the practice of counseling linked to the provision of rapid tests for VIH, syphilis and hepatitis B and C in the context of basic care in a municipality in the southeast region of Paraná. For that, an intervention research was carried out, from the perspective of institutional analysis. The devices used for data production were the semi structured interview with the coordination of the Counseling and Counseling Centers, the observation of the practice of counseling in two Health Units and the accomplishment of a focus group with the nurses and technicians of basic care nursing. Data analysis consisted of analyzers and four lines of analysis, as well as a characterization block in relation to the research participants, the context of basic health care and VIH-SIDA/STI care in the municipality. The first line of analysis shows three analyzers that emerged from the comparative device between two Health Units: family health strategy/basic Health Unit; Work process; Subjective Mobilization of the Worker. The second line of analysis is a discussion through analyzing cases, which revealed the challenges and complexity of the practice of counseling in basic care. The third line of analysis shows the place of science and the university as an institution that aims at extracting data for the construction of knowledge rather than a collective production that also brings contributions to the field. The fourth line of analysis highlights the aspects that go through the practice of counseling in basic care from the forces that cross (sexuality, techniczation/mechanicism, three dimensions of counseling) and mainstream this practice (integrality of basic care; matricial support of the center for testing and counseling. We conclude that the approach to counseling in basic care should be adapted to different contexts, according to the reality and needs of each user.